Using Multimedia Interactive Learning Informatics Materials in Junior High Schools on Increasing Students’ Cognitive Abilities - Puput Tri Anggara; Herman Dwi Surjono (Journal of Education Technology, 2023)
The informatics learning process so far has yet to be completely effective. causing students' abilities and learning outcomes to be low. This research aims to develop interactive learning multimedia products in junior high schools to improve students' cognitive abilities. This type of research is development research. The model used to create products is Alessi and Trollip, which consists of 1) planning, 2) design, and 3) development. Product testing consists of alpha and beta tests, used to determine the level of product feasibility, and effectiveness tests, used to determine the level of product effectiveness on students' cognitive learning outcomes. The product alpha test, product beta test and effectiveness test involved 30 students. To collect data using interviews, observations, questionnaires and tests. The data that has been collected is then analyzed using qualitative descriptive methods. The research results, namely the results of product testing in the alpha test, rated this multimedia in the very feasible category with an average score of 3.75 by media experts and 3.50 by material experts. The beta test results also placed this multimedia in the very doable category with an average score of 3.68 and a Gain score of 0.725, included in the High criteria. It was concluded that interactive learning multimedia is suitable for use in learning. The use of interactive multimedia learning information materials can significantly increase students' learning motivation and cognitive learning achievements.